Effects of sole cropping, intercropping and rotation with legume trap-crops on striga control and maize grain yield in farmers' fields in the Guinea savannas - Kureh, I.; Kamara, A.Y. (International Institute of Tropical Agriculture, 2007)
On-farm trials were conducted in 2001 to 2003 in the northern Guinea savanna of Nigeria to evaluate integrated Striga hermonthica control methods under farmer-managed conditions. These included intercropping a Striga-resistant maize variety with cowpea (Vigna unguiculata L.) and also cropping this maize in rotation with legume trap-crops - soybean (Glycine max (L) Merr.) and cowpea. Intercropping Striga-tolerant maize vaeirty, Acr. 97 TZL Comp. 1-W, with cowpea or rotating it with the soybean cultivar TGX1448-2E) or the cowpea cultivar IT93K452-1 proved effective in reducing Striga incidence and infestation compared with three years of continuously cropped maize as control. Striga incidence was reduced by 73% in intercropped maize, 64% in maize after two years soybean, and by 68% in maize after two years of cowpea than in continuously cropped maize. However, maize grain yield was considerably reduced when intercropped with cowpea, probably due to competition from the cowpea crop. Maize grain yield was 28% higher after one year of soybean and 21% higher after one year of cowpea than in the continuously cropped maize. Maize grain yield was 85% higher after two years of soybean, and 66% higher after two years of cowpea than in the continuously cropped maize.